Urban Visions From Planning Culture to Landscape Urbanism (Springer International Publishing, 2018)
This book is a useful reference in the field of urbanism. It explains how the contemporary city and landscape have been shaped by certain twentieth century visions that have carried over into the twenty-first century. Aimed at both students and professionals, this collection of essays on diverse subjects and cases does not attempt to establish universal interpretations; it rather highlights some outstanding episodes that help us understand why the planning culture has given way to other forms of urbanism, from urban design to strategic urbanism or landscape urbanism. Compared with global interpretations of urbanism based on socioeconomic history or architectural historiography, Urban Visions. From Planning Culture to Landscape Urbanism, aims to present the discipline couched in international contemporary debate and adopt a historic and comparative perspective. The book's contents pertain equally to other related disciplines, such as architecture, urban history, urban design, landscape architecture and geography. Foreword by Rafael Moneo. Carmen Díez Medina, Madrid 1962 Degree in Architecture from the Madrid Polytechnic University (ETSAM UPM), 1989. Ph.D. at the Technische Universität Wien (TU Wien), 1996. Associate Professor of Theory and Architectural History at the School of Engineering and Architecture (EINA) and Coordinator of the PhD Program New Territories in Architecture, University of Zaragoza (Spain). Collaborating architect at Rafael Moneo in Madrid (1996-2001) and previoulsy at Nigst, Hubmann&Vass in Vienna (1990-1996). Javier Monclús, Zaragoza 1951 Degree in Architecture and Ph.D. from the Catalonia Polytechnic University (ETSAB, UPC), 1977. Full Professor of Urbanism at the School of Engineering and Architecture (EINA), University of Zaragoza (Spain), where he has been Chair of the Department of Architecture (2009-2016). Previously, Professor of Urbanism at the Polytechnic University of Catalonia in Barcelona (1980-2005). Member of the Editorial Board of Planning Perspectives. He has worked as a planner and as a consultant in Barcelona and Zaragoza.